2020
DOI: 10.1111/jcmm.14924
|View full text |Cite
|
Sign up to set email alerts
|

First‐trimester blood urea nitrogen and risk of gestational diabetes mellitus

Abstract: Prior studies indicated that urea increased insulin resistance and higher blood urea nitrogen (BUN) was associated with incident diabetes mellitus. However, it remains unclear whether BUN during the first trimester of pregnancy increases risk of gestational diabetes mellitus (GDM). We aimed to investigate the association between first‐trimester BUN and risk of incident GDM. We conducted a prospective, multicenter cohort study of pregnant women. A total of 13 448 eligible pregnant women with measured first‐trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 29 publications
3
15
3
Order By: Relevance
“…The main difference between the study by Feng et al 22 and the present study is the age of the participants (27.63 ± 4.09 vs 31.55 ± 3.91 years, respectively), which may provide a potential explanation for the discrepancy between the studies, particularly due to our finding that…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…The main difference between the study by Feng et al 22 and the present study is the age of the participants (27.63 ± 4.09 vs 31.55 ± 3.91 years, respectively), which may provide a potential explanation for the discrepancy between the studies, particularly due to our finding that…”
Section: Discussioncontrasting
confidence: 84%
“…38 A study in China by Feng et al that included 13,448 eligible pregnant women, of which 2,793 had GDM, reported that elevated UN levels in early pregnancy were positively and dose-responsively correlated with an increased risk of GDM. 22 However, we detected no association between UN and GDM in either our total population or age-stratified subgroups.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Diagnosis of GDM generally occurs at an advanced gestational age, thus limiting preventive strategies. Therefore, there is a growing interest in the initial prediction of GDM [3].…”
Section: Introductionmentioning
confidence: 99%